The Role of Social Media for Islam in Multicultural Society in Bali During the Covid-19 Pandemic - Sunaryo, Fransiska Dewi Setiowati (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This study aims to determine the extent to which Islam uses social media to disseminate information about religion, especially during the pandemic in Bali, in multicultural societies in particular, and Indonesia in general, which experience restrictions on worship. Bali is an area with a multicultural society; how can religious leaders and the government work together to convince people to comply with health protocols and not abandon their worship according to established Islamic teachings? This study uses historical heuristics, criticism, interpretation, and heuristics using sources from journals, books, and interviews with Islamic religious leaders and Muslims in Bali. The results of the study revealed that religious leaders and Muslims in Bali made good use of social media facilities to continue carrying out their worship during the pandemic. Although initially there was resistance, in the end, they accepted and made social media a means of learning for the future.